Early Surveillance and Public Health Emergency Responses Between Novel Coronavirus Disease 2019 and Avian Influenza in China: A Case-Comparison Study - Zhang, Tiantian; Wang, Qian; Wang, Ying; Bai, Ge; Dai, Ruiming; Luo, Li (Frontiers in Public Health, 2021)
Background: The novel coronavirus disease (COVID-19) is spreading rapidly throughout China and the world. Early surveillance and public health emergency disposal are considered crucial to curb this emerging infectious disease. However, studies of COVID-19 on this topic in China are relatively few. Methods: A case-comparison study was conducted using a set of six key time nodes to form a reference framework for evaluating early surveillance and public health emergency disposal between H7N9 avian influenza (2013) in Shanghai, China and COVID-19 in Wuhan, China. Findings: A report to the local Center for Disease Control and Prevention, China, for the first hospitalized patient was sent after 6 and 20 days for H7N9 avian influenza and COVID-19, respectively. In contrast, the pathogen was identified faster in the case of COVID-19 than in the case of H7N9 avian influenza (12 days vs. 31 days). The government response regarding COVID-19 was 10 days later than that regarding avian influenza. The entire process of early surveillance and public health emergency disposal lasted 5 days longer in COVID-19 than in H7N9 avian influenza (46 days vs. 41 days). Conclusions: The identification of the unknown pathogen improved in China between the outbreaks of avian influenza and COVID-19. The longer emergency disposal period in the case of COVID-19 could be attributed to the government’s slower response to the epidemic. Improving public health emergency management could lessen the adverse social effects of emerging infectious diseases and public health crisis in the future.